Preparation method of amphiphilic high-amylose corn grafted starch nanofiber drug-loaded membrane
Through high-linear corn starch graft modification and electrospinning technology, an amphiphilic high-linear corn grafted starch nanofiber drug-loading film was prepared, which solved the problem of poor processability of corn starch in the application of biomedical field, and achieved the effective sustained release of drugs and the stability of drug-loading film.
Patent Information
- Application Number
- CN202411978830.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The application of corn starch in the biomedical field is limited by its "hard and brittle" characteristics and poor processability, which leads to poor drug loading rate, high swelling rate and high water vapor transmittance of the drug, affecting the sustained release effect of the drug.
Through grafting modification of high-linear corn starch, an amphiphilic high-linear corn grafted starch nanofiber drug-loading film was prepared. The modified starch was combined with sustained-release drugs by electrospinning technology to form a nanofiber drug-loading film with excellent drug loading, low swelling rate and low water vapor transmittance.
The appropriate drug loading rate, low swelling rate and low water vapor transmittance of nanofiber drug-loading film are achieved, which significantly improves the sustained release effect of the drug and enhances the stability and reliability of the drug-loading film.
Smart Images

Figure BDA0005221045650000111 
Figure BDA0005221045650000121 
Figure BDA0005221045650000122
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing an amphiphilic high-amylose corn grafted starch nanofiber drug-carrying film. Background Art
[0002] Corn starch, as a common biomass material, has broad application prospects in the field of materials science. Traditionally, corn starch is mainly used in the food industry, for example as a thickener, adhesive, etc. However, with the development of materials science, people gradually realize that corn starch has good renewability, biocompatibility and processability, and therefore began to apply it to a wider range of fields, such as biomedicine, environmental protection and functional materials.
[0003] In the biomedical field, the water solubility and biocompatibility of corn starch materials make it an ideal biodegradable material. For example, corn starch can be used to prepare biodegradable medical packaging materials, drug carriers and tissue engineering scaffolds. It has good biocompatibility and degradation performance, which can reduce the negative impact on the environment and human body. In addition, corn starch also has excellent processability and formability. It can be prepared into functional materials with different structures and properties through various processing methods, such as solution casting, hot pressing molding and nanofiber preparation. In recent years, materials such as nanofiber membranes, microspheres and hydrogels prepared using corn starch have become a research hotspot and show broad application prospects.
[0004] In recent years, with the rapid economic development, oil resources are becoming increasingly scarce and prices are continuing to soar, as well as a series of major environmental pollution problems caused by the processing and preparation of various polymer materials using petrochemical products as the main raw materials. This has led to the application research of corn starch, a natural polymer material that is low-priced, naturally renewable, environmentally friendly, and degradable, and meets the requirements of environmental protection and sustainable development strategies. It has received increasing attention and is widely used in textile warp sizing, papermaking, food, plastics, and medicine. However, there are a large number of glucose ring structures in starch macromolecules, which makes the starch film "hard and brittle". For details, see: Li W, Xu ZZ, Wang ZQ, et al. Tertiary amination / hydroxypropylsulfonation of cornstarch to improve the adhesion-to-fibers and film properties for warp sizing [J]. Fibers and Polymers, 2018, 19 (7): 1386-1394; starch molecules contain a large number of hydroxyl groups, and there are hydroxyl groups on carbons 2, 3, and 6 on each glucose unit, forming a large number of hydrogen bonds within and between molecules. Even if the hydrogen bond itself has a weak force, the huge number of hydrogen bonds makes the connection between molecules very tight, and the molecular movement is difficult, resulting in poor processability of starch. For details, see: Zhu Chengzhang. Research on the structure and modification of electrospun starch nanofibers [D]. Tianjin: Tianjin Polytechnic University, 2017. All these seriously affect the application effect of starch in the above fields. Therefore, in order to meet application requirements, it is often mixed with other synthetic polymers (such as PVA) in actual applications to alleviate the negative effects caused by the poor performance of starch. However, PVA is not environmentally friendly. For details, see: Zhang Xin. Development of environmentally friendly pulp for textiles from hemp stalks and waste hemp fibers [D]. Dalian: Dalian Polytechnic University, 2016, and the prices of these polymers are much higher than starch. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing an amphiphilic high-amylose corn grafted starch nanofiber drug-loaded film. The prepared nanofiber drug-loaded film has a suitable drug loading rate, a low swelling rate, a low water vapor permeability, and a sustained-release effect on the loaded drug.
[0006] In order to solve the above technical problems, the present invention provides a method for preparing an amphiphilic high-amylose corn grafted starch nanofiber drug-loaded film, comprising the following steps:
[0007] (1) Weighing 120 g of high-amylose corn starch by dry weight, and mixing it with alcohol and water in a volume ratio of 6:4 to 9:1 to prepare a starch milk with a mass fraction of 15% to 40%;
[0008] (2) adjusting the pH of the starch milk to 3-4 with dilute hydrochloric acid, transferring it to a four-necked flask, stirring it thoroughly, and heating it in a water bath to 25-45°C;
[0009] (3) After heating in a water bath to the set temperature, nitrogen is introduced for 30 minutes, and under nitrogen protection, 20-40 g of methyl acrylate, 20-40 g of (3-acrylamidopropyl)trimethylammonium chloride, 20-40 mL of 0.5% by mass ammonium ferrous sulfate, and 18.7-37.3 mL of 1.0% by mass aqueous hydrogen peroxide solution are simultaneously added dropwise to the starch milk, and the addition is required to be completed within 30-40 minutes, and then the anaerobic reaction is continued for 3-6 hours;
[0010] (4) After the anaerobic reaction is completed, the pH of the grafted product is adjusted to 6-7 with a 3-10% sodium carbonate aqueous solution, filtered and washed several times, and then the filter cake is crushed and dried in an oven to obtain a grafted starch sample and bagged for later use;
[0011] (5) taking 6 to 13 g of a grafted starch sample, adding 300 to 600 mL of a diluted sodium hypochlorite solution, adjusting the pH to 7, soaking for 1 to 3 hours, washing, filtering, and drying to obtain a chlorinated grafted starch;
[0012] (6) weighing chlorinated grafted starch and dimethyl sulfoxide, dissolving the former in the latter to form a mixed solution, wherein the mass fraction of the chlorinated grafted starch in the mixed solution is 15 to 22%;
[0013] (7) then adding a sustained-release drug to the mixture, the mass of which is 0 to 20% of the mass of the chlorinated grafted starch, and then heating to 60 to 80° C. and stirring with a magnetic stirrer until the mixture becomes transparent, and standing until degassing;
[0014] (8) Adjust the spinning parameters of the electrospinning machine: the spinning environment temperature is 45-65°C, the voltage is 20 kV, the distance between the syringe and the drum is adjusted to 12-22 cm, the propulsion speed is 1-2 mL / h, and the time is 5-10 h. After the adjustment is completed, the spinning solution is loaded into the syringe and degassed. The electrospinning machine is turned on and the spinning solution is ejected from the syringe port at the set propulsion speed. The spinning solution is stretched and refined in the charged jet formed by the high-voltage electric field and falls onto the release paper on the surface of the rolling drum. After 5-10 hours, an amphiphilic high-linear corn grafted starch nanofiber drug-loaded film can be spun on the surface of the release paper.
[0015] Preferably, the sustained-release drug in step (7) can be one of aspirin, mesalamine, doxorubicin, sulpiride, ibuprofen, acetaminophen, benolate, and indomethacin.
[0016] Preferably, in step (3), the total amount of the two monomers, methyl acrylate and (3-acrylamidopropyl)trimethylammonium chloride, added is 60 g.
[0017] Advantages of the present invention: The nanofiber drug-loaded film prepared by the preparation method of the amphiphilic high-amylose corn grafted starch nanofiber drug-loaded film of the present invention has a suitable drug-loading rate, a low swelling rate, a low water vapor permeability, and a sustained-release effect on the loaded drug. The lower swelling performance makes it have higher stability and reliability in practical applications. The water vapor permeability refers to the rate at which water vapor passes through a material per unit time, and is one of the important indicators for measuring the air permeability of a material. The air permeability can affect the release rate and release behavior of the drug in the carrier, and further affect the efficacy and treatment effect of the drug. Therefore, the nanofiber drug-loaded film prepared by the method of the present invention has a good drug sustained-release effect. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Surface scanning image of grafted starch in Example 2.
[0019] Figure 2 This is the SEM picture of native starch.
[0020] Figure 3 This is the SEM image of the grafted starch in Example 2.
[0021] Figure 4 It is the infrared spectra of native starch and grafted starch in Example 2.
[0022] Figure 5 The left side is the SEM image of sample 0, and the right side is the SEM image of sample 1.
[0023] Figure 6 The left side is the SEM image of sample 2, and the right side is the SEM image of sample 3.
[0024] Figure 7 These are the XRD patterns of native starch film, native starch drug-loaded film, grafted starch film and grafted starch drug-loaded film.
[0025] Figure 8 This is a graph showing the porosity of the drug-loaded membrane changing with the grafting rate.
[0026] Fig. 9 It is a schematic diagram of the swelling rate results of the drug-loaded film.
[0027] Fig.10 It is a schematic diagram of the water vapor permeability results of the drug-loaded film.
[0028] Fig.11 is the standard curve of aspirin.
[0029] Fig.12This is a schematic diagram of the cumulative drug release rate results of the drug-loaded film. DETAILED DESCRIPTION
[0030] Embodiment 1:
[0031] The method for preparing the amphiphilic high-amylose corn grafted starch nanofiber drug-carrying film comprises the following steps:
[0032] (1) Weighing 120 g of high-amylose corn starch by dry weight, and mixing it with alcohol and water in a volume ratio of 6:4 to prepare a starch milk with a mass fraction of 15%;
[0033] (2) Adjust the pH of the starch milk to 3-4 with dilute hydrochloric acid, transfer it to a four-necked flask, stir it thoroughly, and heat it in a water bath to 25°C;
[0034] (3) After heating to the set temperature in a water bath, nitrogen was introduced for 30 min and 20 g of methyl acrylate, 20 g of (3-acrylamidopropyl)trimethylammonium chloride, 20 mL of 0.5% by mass ammonium ferrous sulfate, and 18.7 mL of 1.0% by mass hydrogen peroxide aqueous solution were simultaneously added dropwise to the starch milk under nitrogen protection, and the addition was required to be completed within 30 to 40 min, and then the reaction was continued in anoxic conditions for 3 hours;
[0035] (4) After the anaerobic reaction is completed, the pH of the grafted product is adjusted to 6-7 with a 3% sodium carbonate aqueous solution, filtered and washed several times, and then the filter cake is crushed and dried in an oven to obtain a grafted starch sample and bagged for later use;
[0036] (5) taking 6 g of grafted starch sample, adding 300 mL of diluted sodium hypochlorite solution, adjusting the pH to 7, soaking for 1 h, washing, filtering, and drying to obtain chlorinated grafted starch;
[0037] (6) weighing chlorinated grafted starch and dimethyl sulfoxide, dissolving the former in the latter to form a mixed solution, wherein the mass fraction of the chlorinated grafted starch in the mixed solution is 15%;
[0038] (7) then adding the sustained-release drug mesalazine to the mixture at a mass of 5% of the mass of the chlorinated grafted starch, then heating to 60° C. and stirring with a magnetic stirrer until the mixture becomes transparent, and standing until degassing;
[0039] (8) Adjust the spinning parameters of the electrospinning machine: the spinning environment temperature is 45 °C, the voltage is 20 kV, the distance between the syringe and the drum is adjusted to 12 cm, the propulsion speed is 1 mL / h, and the time is 5 h. After the adjustment is completed, the spinning solution is loaded into the syringe and degassed. The electrospinning machine is turned on and the spinning solution is ejected from the syringe port at the set propulsion speed. The spinning solution is stretched and refined in the charged jet formed by the high-voltage electric field and falls onto the release paper on the surface of the rolling drum. After 5 hours, an amphiphilic high-linear corn grafted starch nanofiber drug-loaded film can be spun on the surface of the release paper.
[0040] The sample was tested and the grafting rate of methyl acrylate was 4.12%, and the grafting rate of (3-acrylamidopropyl)trimethylammonium chloride was 3.87%.
[0041] Embodiment 2:
[0042] The method for preparing the amphiphilic high-amylose corn grafted starch nanofiber drug-carrying film comprises the following steps:
[0043] (1) Weighing 120 g of high-amylose corn starch by dry weight, and mixing it with alcohol and water in a volume ratio of 8:2 to prepare a starch milk with a mass fraction of 30%;
[0044] (2) Adjust the pH of the starch milk to 3-4 with dilute hydrochloric acid, transfer it to a four-necked flask, stir it thoroughly, and heat it in a water bath to 30°C;
[0045] (3) After heating to the set temperature in a water bath, nitrogen was introduced for 30 min and 30 g of methyl acrylate, 30 g of (3-acrylamidopropyl)trimethylammonium chloride, 30 mL of 0.5% ammonium ferrous sulfate, and 28 mL of 1.0% aqueous hydrogen peroxide solution were simultaneously added dropwise to the starch milk under nitrogen protection, and the addition was required to be completed within 30 to 40 min, and then the reaction was continued in anoxic conditions for 5 hours;
[0046] (4) After the anaerobic reaction is completed, the pH of the grafted product is adjusted to 6-7 with a 6% sodium carbonate aqueous solution, filtered and washed several times, and then the filter cake is crushed and dried in an oven to obtain a grafted starch sample and bagged for later use;
[0047] (5) taking 10 g of grafted starch sample, adding 400 mL of diluted sodium hypochlorite solution, adjusting the pH to 7, soaking for 2 h, washing, filtering, and drying to obtain chlorinated grafted starch;
[0048] (6) weighing chlorinated grafted starch and dimethyl sulfoxide, dissolving the former in the latter to form a mixed solution, wherein the mass fraction of the chlorinated grafted starch in the mixed solution is 18%;
[0049] (7) then adding aspirin, a sustained-release drug, to the mixture at a mass of 10% of the mass of the chlorinated grafted starch, and then heating to 70° C. and stirring with a magnetic stirrer until the mixture becomes transparent, and standing until degassing;
[0050] (8) Adjust the spinning parameters of the electrospinning machine: the spinning environment temperature is 60°C, the voltage is 20 kV, the distance between the syringe and the drum is adjusted to 15 cm, the propulsion speed is 1 mL / h, and the time is 7 h. After the adjustment is completed, the spinning solution is loaded into the syringe and degassed. The electrospinning machine is turned on and the spinning solution is ejected from the syringe port at the set propulsion speed. The spinning solution is stretched and refined in the charged jet formed by the high-voltage electric field and falls onto the release paper on the surface of the rolling drum. After 7 hours, an amphiphilic high-linear corn grafted starch nanofiber drug-loaded film can be spun on the surface of the release paper.
[0051] The sample was tested and the grafting rate of methyl acrylate was 5.26%, and the grafting rate of (3-acrylamidopropyl)trimethylammonium chloride was 8.28%.
[0052] Embodiment three:
[0053] The method for preparing the amphiphilic high-amylose corn grafted starch nanofiber drug-carrying film comprises the following steps:
[0054] (1) Weighing 120 g of high-amylose corn starch by dry weight, and mixing it with alcohol and water in a volume ratio of 9:1 to prepare a starch milk with a mass fraction of 40%;
[0055] (2) Adjust the pH of the starch milk to 3-4 with dilute hydrochloric acid, transfer it to a four-necked flask, stir it thoroughly, and heat it in a water bath to 45°C;
[0056] (3) After heating in a water bath to the set temperature, nitrogen was introduced for 30 min and 40 g of methyl acrylate, 40 g of (3-acrylamidopropyl)trimethylammonium chloride, 40 mL of 0.5% by mass ammonium ferrous sulfate, and 37.3 mL of 1.0% by mass hydrogen peroxide aqueous solution were simultaneously added dropwise to the starch milk under nitrogen protection, and the addition was required to be completed within 30 to 40 min, and then the reaction was continued in anoxic conditions for 6 hours;
[0057] (4) After the anaerobic reaction is completed, the pH of the grafted product is adjusted to 6-7 with a 10% sodium carbonate aqueous solution, filtered and washed several times, and then the filter cake is crushed and dried in an oven to obtain a grafted starch sample and bagged for later use;
[0058] (5) taking 13 g of grafted starch sample, adding 600 mL of diluted sodium hypochlorite solution, adjusting the pH to 7, soaking for 3 h, washing, filtering, and drying to obtain chlorinated grafted starch;
[0059] (6) weighing chlorinated grafted starch and dimethyl sulfoxide, dissolving the former in the latter to form a mixed solution, wherein the mass fraction of the chlorinated grafted starch in the mixed solution is 22%;
[0060] (7) then adding the sustained-release drug acetaminophen to the mixed solution at a mass of 20% of the mass of the chlorinated grafted starch, then heating to 80° C. and stirring with a magnetic stirrer until the mixed solution becomes transparent, and then standing until degassing;
[0061] (8) Adjust the spinning parameters of the electrospinning machine: the spinning environment temperature is 65 ° C, the voltage is 20 kV, the distance between the syringe and the drum is adjusted to 22 cm, the propulsion speed is 2 mL / h, and the time is 10 h. After the adjustment is completed, the spinning solution is loaded into the syringe and degassed. The electrospinning machine is turned on and the spinning solution is ejected from the syringe port at the set propulsion speed. The spinning solution is stretched and refined in the charged jet formed by the high-voltage electric field and falls onto the release paper on the surface of the rolling drum. After 10 hours, an amphiphilic high-amylose corn grafted starch nanofiber drug-loaded film can be spun on the surface of the release paper.
[0062] The sample was tested and the grafting rate of methyl acrylate was 7.85%, and the grafting rate of (3-acrylamidopropyl)trimethylammonium chloride was 11.01%.
[0063] Characterization and analysis of grafted starch
[0064] 1. EDS analysis
[0065] To confirm that the (3-acrylamidopropyl)trimethylammonium chloride unit has been successfully grafted into the high-amylose corn starch molecule, the grafted starch particles obtained in step (4) of Example 2 were subjected to elemental analysis using EDS technology. The results are shown in Figure 1 .Depend on Figure 1 It can be seen that the elemental composition of the grafted starch granules is mainly C and O elements, and also contains N and Cl elements, which proves that the (3-acrylamidopropyl)trimethylammonium chloride unit has been successfully grafted into the high-amylose corn starch molecular chain.
[0066] 2. SEM analysis
[0067] Figure 2 and Figure 3 The SEM images of the original starch and the grafted starch obtained in step (4) of Example 2 are shown. As shown in the figure, the surface morphology of the two starches is quite different. Specifically, the surface of the original starch is smooth and full and round, while the surface of the grafted starch sample particles is mostly uneven and has a papillary structure, indicating that the grafting modification of high-amylose starch will cause dissolution on the surface of its particles, causing damage to the surface of the particles.
[0068] 3. Infrared spectroscopy analysis
[0069] See also Figure 4 , Figure 4 The infrared spectra of the original starch and the grafted starch obtained in step (4) of Example 2 are shown in FIG. -1 The peak at is the stretching vibration absorption peak of C=O, indicating the successful grafting of methyl acrylate units.
[0070] Comparative experiment of amphiphilic high-amylose corn grafted starch nanofiber drug-loaded film
[0071] In order to prove the beneficial effects of the amphiphilic high-amylose corn grafted starch nanofiber drug-loaded film prepared by the method of the present invention, the following comparative experiment is used to prove it. The comparative experiment is based on the scheme of Example 2, wherein:
[0072] In step (3), the solution in which the input amounts of methyl acrylate and (3-acrylamidopropyl)trimethylammonium chloride are both 0 is the blank control of the prior art, and the obtained product is recorded as sample 0;
[0073] In step (3), the solution in which the amount of methyl acrylate and (3-acrylamidopropyl)trimethylammonium chloride added was 20 g was experimental group 1, and the obtained product was recorded as sample 1;
[0074] In step (3), the solution in which the amount of methyl acrylate and (3-acrylamidopropyl)trimethylammonium chloride added was 30 g was experimental group 1, and the obtained product was recorded as sample 2;
[0075] In step (3), the solution in which the input amounts of both methyl acrylate and (3-acrylamidopropyl)trimethylammonium chloride monomers are 40 g is experimental group 1, and the obtained product is recorded as sample 3.
[0076] 1. SEM morphology comparison
[0077] See also Figure 5 and Figure 6 , Figure 5 The left side is the SEM image of sample 0. Figure 5 The right side is the SEM image of sample 1. Figure 6 The left side is the SEM image of sample 2. Figure 6 On the right is the SEM image of sample 3. It can be seen from the figure that the surfaces of the nanofiber drug-loaded membranes of the four samples are basically smooth, and there is no obvious polymer particle residue, indicating that the samples have good compatibility with aspirin; compared with the ungrafted sample 0, the fiber diameter distribution of the grafted samples is uneven.
[0078] 2. XRD results analysis
[0079] The crystallinity of the samples was investigated by XRD analysis of the nanofiber membranes. Figure 7 As shown, Figure 7 The left side in the middle is the XRD graph of the fiber membrane directly spun from sample 0 native starch without adding drugs and the drug-loaded membrane of sample 0 native starch. Figure 7 On the middle right are the XRD patterns of the fiber membrane directly spun from the grafted starch of sample 2 without adding drugs and the grafted starch drug-loaded membrane. It can be seen from the figure that compared with the nanofiber membrane without aspirin loading, the diffraction peaks of the XRD pattern of the drug-loaded membrane are basically consistent with it, and no new drug characteristic peaks appear, indicating that aspirin has been successfully wrapped inside the nanofibers.
[0080] 3. Porosity analysis
[0081] Porosity refers to the proportion of pores in the drug-loaded membrane, which directly affects the release rate and amount of the drug in the drug-loaded membrane. By testing the porosity, the drug loading and release performance of the drug-loaded membrane can be evaluated, providing a basis for the rational design and optimization of the controlled release process of the drug. Generally speaking, the smaller the porosity, the slower the drug release and the better the drug sustained release performance. Figure 8 It can be seen that the porosity of grafted starch samples 1, 2, and 3 is smaller than that of sample 0. Among them, sample 2 (total monomer input is 60g) has the lowest porosity of 41.2% among the three grafted samples. The reason for this may be that the fiber diameter of sample 2 is relatively large and the specific surface area is small, resulting in a decrease in the gap between single fibers and a decrease in porosity.
[0082] 4. Analysis of swelling performance results
[0083] Swelling performance testing can help evaluate the stability of drug-loaded films under different solution conditions. Drug sustained-release systems may be affected by different solution environments in the human body or the environment, such as different pH values, temperatures, or solution components. By simulating these conditions and testing the swelling performance of drug-loaded films, their stability and reliability in practical applications can be evaluated. Swelling performance results are shown in Fig. 9 It can be seen that the swelling rate of the grafted starch drug-loaded film is significantly lower than that of the blank control. With the increase of the grafting rate, the swelling rate shows a trend of gradual decrease, from 697% to 489%. The reason may be that the introduction of two grafted monomer units makes the starch hydrophobic as a whole, so as to increase the grafting rate, the hydrophobicity is enhanced, the binding effect between starch and water molecules is reduced, and the swelling rate is reduced.
[0084] 5. Analysis of water vapor transmission rate results
[0085] The significance of testing the water vapor permeability of nanofiber drug-loaded membranes is to evaluate their air permeability during application. Water vapor permeability refers to the rate at which water vapor passes through a material per unit time, and is one of the important indicators for measuring the air permeability of a material. Air permeability can affect the release rate and release behavior of the drug in the carrier, and thus affect the efficacy and treatment effect of the drug. The water vapor permeability results are as follows: Fig.10 As shown. It can be seen that the water vapor permeability of the grafted starch drug-loaded film is lower than that of sample 0, and the porosity is positively correlated with the water vapor permeability, that is, the higher the porosity, the faster the rate at which water vapor passes through the film per unit time.
[0086] 6. Analysis of drug sustained-release performance results
[0087] Calibration and drawing of aspirin standard curve
[0088] First, weigh an appropriate amount of aspirin and dissolve it in PBS buffer to obtain standard solutions of 5 mg / L, 10 mg / L, 25 mg / L, 50 mg / L, and 100 mg / L, respectively. Next, use an ultraviolet spectrophotometer to test the full wavelength absorbance of these standard solutions, and then measure the absorbance at a wavelength of 296 nm. Draw a graph with the absorbance as the y-axis and the aspirin solution concentration as the x-axis ( Fig.11 ), and obtain the aspirin standard curve. Fig.11 It can be seen that when the aspirin concentration is in the range of 5-100 mg / L, the absorbance and concentration show a good linear relationship. The standard curve equation is Y=0.0023X+0.0157, and the correlation coefficient R 2 is 0.9978.
[0089] Analysis of sustained release performance results
[0090] Generally speaking, in order to treat some chronic diseases that are difficult to eradicate at one time, such as cardiovascular disease, cancer, diabetes, etc., in order to achieve long-term drug release and continuous drug administration, nanofiber membranes with a lower sustained release rate are the best choice. Fig.12 As shown. It can be seen that the cumulative release rate of the ungrafted sample 0 is close to 40% after 2 hours, while the cumulative drug release rate of the grafted sample is significantly lower than that of sample 0, and the sustained release rate of sample 2 (the total amount of grafted monomer input is 60g) is the lowest, and the drug release is the most sustained. The reason for the analysis is that drug release is usually achieved through diffusion on the surface of nanofibers. Sample 2 has the largest nanofiber diameter, the least number of fibers per unit area, the smallest effective area for drug release, and the lowest sustained release rate.
[0091] In the above characterization experiments and comparative experiments, the specific operation steps and calculation methods are as follows:
[0092] SEM morphology characterization:
[0093] After the nanofiber membrane samples were sprayed with gold, the surface morphology was observed using a Guoyi Quantum SEM 3200 scanning electron microscope.
[0094] X-ray diffraction analysis:
[0095] Cut 2×2cm 2 The sample was placed on the sample stage of the X-ray diffractometer, and the surface of the sample was ensured to be flat. A German Bruker D8 Advance X-ray diffractometer was used, the tube voltage of the X-ray was set to 40 kV, a copper target was used for scanning at 30 mA current, and the scanning range was 10-80°. The X-ray diffractometer was started, data collection began, the diffraction pattern was drawn, and the crystal structure analysis was performed by comparing the diffraction pattern of the known standard sample.
[0096] Infrared spectroscopy characterization:
[0097] The chemical structure of the nanofiber membrane was analyzed by potassium bromide tablet method on IRPrestige-21 Fourier transform infrared spectrometer with a scanning range of 4000-500 cm -1 .
[0098] Water vapor transmission rate test:
[0099] 10 mL of PBS buffer was placed in a cylindrical glass bottle. The membrane sample was cut into a size (S) approximately equal to the cross-sectional area of the container mouth. The container mouth was covered with the membrane, sealed with tape and weighed as m0. An open glass bottle containing 10 mL of PBS buffer was used as a blank control group. After that, the entire device was placed in an oven at 37°C to maintain relatively low humidity conditions. It was taken out and weighed every hour and recorded as m n , twice in total.
[0100]
[0101] Where: T——interval between two times of mass reduction
[0102] S——the area of the mouth of the glass bottle (0.000706m 2 )
[0103] Swelling performance test:
[0104] Cut the sample into 2cm×2cm size. Let it stand for 24 hours at 25℃ and 65% relative humidity, weigh the sample and record it as m0; put the membrane into PBS buffer solution 40 times its own weight, and place it in a 37℃ oven for 24 hours to reach saturation. After standing and hanging for 30 seconds, the wet weight of the sample is recorded as m1. Calculate the swelling rate according to the formula:
[0105]
[0106] Porosity test:
[0107] Cut a 3cm×3cm nanofiber membrane sample and let it stand at room temperature to achieve a humidity equilibrium state equivalent to the environment to prevent water evaporation or absorption from causing changes in the porosity of the sample. Use an electronic balance to accurately weigh the nanofiber membrane sample and record it as m0. Place the weighed nanofiber membrane sample in an ethanol solution and allow it to be completely immersed for 1 hour. Then take out the soaked nanofiber membrane sample and wipe off the excess solution on the surface with a paper towel. Use an electronic balance to accurately weigh the treated nanofiber membrane sample again and record it as m1. Use the following formula to calculate the porosity (p, %):
[0108]
[0109] Determination of drug sustained release performance:
[0110] Preparation of PBS solution: weigh 8.0g NaCl, 0.2g KCl, 1.44g Na2HPO4, and 0.24g KH2PO4 and dissolve them in 800mL distilled water. Use HCl to adjust the solution to 7.4, and finally add distilled water to make up to 1L to obtain 0.01mol / L PBS buffer.
[0111] Determination of sustained-release performance: Take 100 mL of PBS sustained-release solution, cut and weigh a certain mass of fiber membrane, put it into PBS solution and keep it at a constant temperature of 37°C, take out 6 mL at 1 h, 2 h, 3 h, 6 h, and 9 h after adding PBS, and measure its absorbance at 296 nm wavelength with an ultraviolet spectrophotometer, and add 6 mL every time 6 mL is taken out. Calculate the cumulative release of the drug based on the aspirin standard curve, and then draw the cumulative release curve of the drug.
[0112] In the above embodiments, characterization experiments and comparative experiments,
[0113] High amylose corn starch was produced by Shanghai Quanwang Biotechnology Co., Ltd., with a moisture content of 13.43%. The main experimental reagents are shown in Table 1.
[0114] Table 1 Main experimental reagents
[0115] Experimental raw materials Specification Manufacturer Methyl acrylate Analytical grade Maclean Chemical Reagents Ltd. (3-Acrylamidopropyl)trimethylammonium chloride Analytical grade Maclean Chemical Reagents Ltd. Dimethyl sulfoxide Analytical grade Maclean Chemical Reagents Ltd. Anhydrous ethanol Analytical grade Shanghai Titan Technology Co., Ltd. Ammonium ferrous sulfate Analytical grade Tianjin Komiou Chemical Reagent Co., Ltd. Hydrogen Peroxide Analytical grade Feijing Biotechnology Co., Ltd. Sodium hypochlorite Analytical grade Maclean Chemical Reagents Ltd. Sodium chloride Analytical grade Guangdong Guanghua Technology Co., Ltd. Potassium chloride Analytical grade Maclean Chemical Reagents Ltd. Potassium dihydrogen phosphate Analytical grade Maclean Chemical Reagents Ltd. Disodium hydrogen phosphate dodecahydrate Analytical grade Shanghai BiDe Pharmaceutical Technology Co., Ltd. aspirin Analytical grade Maclean Chemical Reagents Ltd.
Claims
1. A method for preparing an amphiphilic high-amylose corn grafted starch nanofiber drug-loaded film, characterized in that: The following steps are involved: (1) Weighing 120 g of high-amylose corn starch by dry weight, and mixing it with alcohol and water in a volume ratio of 6:4 to 9:1 to prepare a starch milk with a mass fraction of 15% to 40%; (2) adjusting the pH of the starch milk to 3-4 with dilute hydrochloric acid, transferring it to a four-necked flask, stirring it thoroughly, and heating it in a water bath to 25-45°C; (3) After heating in a water bath to the set temperature, nitrogen is introduced for 30 minutes, and under nitrogen protection, 20-40 g of methyl acrylate, 20-40 g of (3-acrylamidopropyl)trimethylammonium chloride, 20-40 mL of 0.5% by mass ammonium ferrous sulfate, and 18.7-37.3 mL of 1.0% by mass aqueous hydrogen peroxide solution are simultaneously added dropwise to the starch milk, and the addition is required to be completed within 30-40 minutes, and then the anaerobic reaction is continued for 3-6 hours; (4) After the anaerobic reaction is completed, the pH of the grafted product is adjusted to 6-7 with a 3-10% sodium carbonate aqueous solution, filtered and washed several times, and then the filter cake is crushed and dried in an oven to obtain a grafted starch sample and bagged for later use; (5) taking 6 to 13 g of a grafted starch sample, adding 300 to 600 mL of a diluted sodium hypochlorite solution, adjusting the pH to 7, soaking for 1 to 3 hours, washing, filtering, and drying to obtain a chlorinated grafted starch; (6) weighing chlorinated grafted starch and dimethyl sulfoxide, dissolving the former in the latter to form a mixed solution, wherein the mass fraction of the chlorinated grafted starch in the mixed solution is 15 to 22%; (7) then adding a sustained-release drug to the mixture, the mass of which is 0 to 20% of the mass of the chlorinated grafted starch, and then heating to 60 to 80° C. and stirring with a magnetic stirrer until the mixture becomes transparent, and standing until degassing; (8) Adjust the spinning parameters of the electrospinning machine: the spinning environment temperature is 45-65°C, the voltage is 20 kV, the distance between the syringe and the drum is adjusted to 12-22 cm, the propulsion speed is 1-2 mL / h, and the time is 5-10 h. After the adjustment is completed, the spinning solution is loaded into the syringe and degassed. The electrospinning machine is turned on and the spinning solution is ejected from the syringe port at the set propulsion speed. The spinning solution is stretched and refined in the charged jet formed by the high-voltage electric field and falls onto the release paper on the surface of the rolling drum. After 5-10 hours, an amphiphilic high-linear corn grafted starch nanofiber drug-loaded film can be spun on the surface of the release paper.
2. The method for preparing the amphiphilic high-amylose corn grafted starch nanofiber drug-loaded film according to claim 1, characterized in that: The sustained-release drug in step (7) can be one of aspirin, mesalamine, doxorubicin, sulpiride, ibuprofen, acetaminophen, benolate, and indomethacin.
3. The method for preparing the amphiphilic high-amylose corn grafted starch nanofiber drug-loaded film according to claim 1, characterized in that: In the step (3), the total amount of the two monomers, methyl acrylate and (3-acrylamidopropyl)trimethylammonium chloride, added is 60 g.